Implementación de un sistema de gestión administrativa utilizando la metodología SCRUM para la secretaria de la Universidad Técnica de Cotopaxi extensión La Maná para el año 2014 - Bonilla González, Manuel Andrés (2015)
The following research work was conducted at the Cotopaxi Technical University Estension La Maná, using the quantitative method which was favorable with 75% of the implementation of an administrative management system secretary; we use the Scrum methodology based on an incremental process with schedules of activities to perform the steps of the software in a predetermined time. Visual basic 2010 platform allowed us to develop a high quality interface with a development model based on objects using a common data system and these can be reused in order where they need.